Penggunaan Konjungsi Subordinatif dalam Kumpulan Cerita Rakyat Belitung - Resgita, Betta (Universitas Suryakanca, 2022)
Artikel ini dimaksudkan untuk mendeskripsikan hubungan makna konjungsi subordinatif dalam kumpulan cerita rakyat Belitung berjudul Cerite Kampoeng dari Kampoeng Halamanoleh Bule Sahib. Penelitian merupakan penelitian deskriptif kualitatif. Subjek penelitian yaitu kumpulan cerita rakyat dengan objek konjungsi subordinatif. Pengumpulan data dilakukan dengan menggunakan metode simak dengan teknik dasar sadap serta teknik lanjutan simak bebas libat cakap dan catat. Hasil penelitian menunjukkan ditemukan 14 hubungan makna konjungsi subordinatif. Hubungan makna waktu 265 data, makna syarat 24 data, makna pengandaian enam data, makna tujuan 174 data, makna konsesif 21 data, makna pemiripan 11 data, makna penyebaban 70 data, makna akibat sembilan data, makna cara sembilan data, makna alat enam data, makna komplementasi atau penjelas 15 data, makna atributif atau pelengkap 38 data, makna perbandingan lima data, dan makna optatif atau harapan dua data..Katakunci: cerita rakyat; hubungan; konjungsi; makna; subordinatifAbstract:This article aims to describe the relationship between the meaning of subordinating conjunctions in a collection of Belitung folk tales entitledâ€ Cerite Kampoeng dari Kampoeng Halamanâ€ by Bule Sahib. This research is qualitative descriptive research. The research subject is a collection of folk tales with subordinate conjunctions as objects. Data collection was carried out using the listening and recording method, followed by non-participant conversation and note-taking. The results show that there were 14 meaning relationships of subordinating conjunctions. Meaning of time 265 data, the meaning of condition 24 data, the meaning of presupposition 6 data, meaning of purpose 174 data, meaning of concessional 21 data, the meaning of resemblance to 11 data, the meaning of cause 70 data, the meaning of effect 9 data, the meaning of manner 9 data, the meaning of means 6 data, the meaning of complementation or explanation 15 data, the meaning of attributive or complementary 38 data, meaning of comparison 5 data, andÂ meaning of optative or hope 2 data.Keywords: folklore; connection; conjunction; mean; subordinate